Atlas of the Rock-Forming Minerals in Thin Section. - MacKenzie, W. S. (Taylor and Francis, 2014)
'Hurray for Mackenzie and Guilford for at last we have a pictorial guide to the rock-forming minerals! ... such feasts of colour in mineralogy books are rare ... an admirable guide'New Scientist.